THE MICRO PPM POLICY FOR MICRO SMALL MEDIUM ENTERPRISES (MSME) PERFORMERS AT THE TIME OF THE COVID-19 PANDEMIC (A CRITICAL ETHNOGRAPHIC STUDY) - Sri Andika Putri; Hendrik Suhendri; Risna Ningsih (Yayasan Education and Social Center, 2022)
The Covid-19 pandemic has disrupted not only the business performance of the large business sector but also has implications for the MSME sector. This research was conducted to develop the concept of the meaning of the Micro PPM Policy among MSME actors in the city of Malang under the values, ideas, and business practices carried out by MSME actors. Besides looking for a